Analisis Hukum Islam terhadap Investasi Berbasis Syariah di Era Digital - Siti Sopiani; Hermawati; Muliani (Prodi Hukum Ekonomi Syariah (Muamalah), 2025)
This study aims to analyze the Islamic legal aspects of Sharia-compliant investments in the digital era, highlighting the challenges and opportunities in applying Sharia principles amidst rapidly evolving technologies. Digital transformation has fundamentally changed the investment landscape, creating an urgent need for regulatory adaptation that can accommodate technological innovation without compromising adherence to Sharia principles. The research employs a qualitative approach with a focus on comprehensive document analysis, reviewing academic literature, legal regulations and policies, Islamic scholar fatwas, and current research reports. The findings indicate that while technologies such as blockchain, smart contracts, and digital investment platforms offer tremendous potential to enhance transparency, efficiency, and accessibility in Sharia-compliant investments, significant challenges remain that require serious attention. These challenges include adaptive regulatory adjustments, strengthening consumer protection systems, international legal harmonization, and improving digital and Sharia literacy among investors. This study contributes to the development of more adaptive and inclusive regulatory frameworks for Sharia-compliant investments and underscores the urgency of comprehensive education and international collaboration in addressing the complexities of digital Sharia-compliant investment issues in the future.